Relative efficiency of modified urea fertilizers for young rubber plants - Karthikakuttyamma M; Mathew M; Shyamala V K; Suresh P R; Varghese Anna (Indian Journal of Natural Rubber Research, 1994)
Different modified forms of urea, viz., ureaform, neem extract, mixed urea, neem coated urea and neem cake mixed urea were compared along with prilled urea for their efficiency in the growth and development of young Hevea plants in a glass house experiment. A no nitrogen control was also included. The study revealed that ureaform is the best source of nitrogen with respect to growth and apparent recovery of applied N. All the modified forms were effective in increasing the root and shoot growth of the plants. When N is not applied, more than half of the total biomass is diverted for the development of roots. Similar trend was noticed in the case of N partitioning also. If N is applied a good share of it gets translocated to the leaves. Concentration of N in the leachate could be significantly reduced when urea is coated with neem. In all the forms, the maximum flux of N in leachate was observed at the 15th day after fertilizer application.
Keywords: Apparent nitrogen recovery; Dry matter partitioning; Hevea brasiliensis; Leaching loss; Nitrogen; Slow release fertilizer